2016 International Conference on Biometrics (ICB) 2016
DOI: 10.1109/icb.2016.7550096
|View full text |Cite
|
Sign up to set email alerts
|

IrisSeg: A fast and robust iris segmentation framework for non-ideal iris images

Abstract: This paper presents a state-of-the-art iris segmentation framework specifically for non-ideal irises. The framework adopts coarse-to-fine strategy to localize different boundaries. In the approach, pupil is coarsely detected using an iterative search method exploiting dynamic thresholding and multiple local cues. The IntroductionIris is considered one of the most accurate biometrics because of its stability over long time, non-invasiveness, and unique pattern [1]. The accuracy of iris localization, decides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…However, very few researchers have addressed these two databases for segmentation purposes due to unavailability of ground-truth images. To compare with other researchers, Gangwar et al [ 84 ] used various algorithms such as GST [ 85 ], Osiris [ 86 ], WAHET [ 87 ], IFFP [ 88 ], CAHT [ 89 ], Masek [ 90 ], and integro-differential operator (IDO) [ 25 ] with the same database. Therefore, for comparison, the comparative results with these algorithms are presented in Table 7 , and it can be found that the proposed IrisDenseNet outperforms other methods.…”
Section: Resultsmentioning
confidence: 99%
“…However, very few researchers have addressed these two databases for segmentation purposes due to unavailability of ground-truth images. To compare with other researchers, Gangwar et al [ 84 ] used various algorithms such as GST [ 85 ], Osiris [ 86 ], WAHET [ 87 ], IFFP [ 88 ], CAHT [ 89 ], Masek [ 90 ], and integro-differential operator (IDO) [ 25 ] with the same database. Therefore, for comparison, the comparative results with these algorithms are presented in Table 7 , and it can be found that the proposed IrisDenseNet outperforms other methods.…”
Section: Resultsmentioning
confidence: 99%
“…These are the off-axis subset and off-axis with unconstrained condition subset for Bath800 and CASIA Thousand and the off-axis subset for UBIRIS v2, as described in the section 2.3.3. In continuance it is compared with the segmentation results on these samples from the methods: SPDNN [43], IrisSeg [84] and OSIRIS [85]. The test set of the augmented samples is used to test the network and the other methods.…”
Section: Discussionmentioning
confidence: 99%
“…The IRISSEG [46] framework was designed specifically for non-ideal irises and is based on adaptive filtering, following a coarse-to-fine strategy. The authors emphasize that this approach does not require adjustment of parameters for different datasets.…”
Section: Benchmarksmentioning
confidence: 99%